Neuronal Networks and Continuous Spikes and Waves During Slow Sleep - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Haemodynamic changes associated with epileptic activity were investigated at Christian-Albrechts-University, Kiel, Germany, using simultaneous acquisitions of EEG and functional MRI in 12 children with symptomatic and cryptogenic continuous spikes and waves during slow sleep (CSWSS).